(untitled) (Annals of Medical Research, 2023)
Aim: In the current study, we purposed to examine the role of insufficient weight gain after GDM diagnosis in small for gestational age (SGA) and other adverse perinatal outcomes. Materials and Methods: This retrospective cohort study conducted in a referral center over a 5-year period from 2017 through 2022 and 260 pregnant women who met the inclusion criteria were classified as insufficient weight gain (n:68) or appropriate weight gain as a control group (n:192) based on the United States Institute of Medicine (IOM) recommendations for body mass index as calculated by gestational weight gain per week after a diagnosis of GDM. Results: Maternal demographic characteristics and delivery outcomes were similar between groups. BMI at the first visit, BMI at GDM screening, and BMI at delivery were significantly higher in the appropriate gain group compared to the insufficient gain group. After adjusting for the variables, we observed that insufficient weight gain after a GDM diagnosis was not associated with SGA (adjusted odds ratio [aOR], 1.964; 95% confidence interval [CI], 0.306–12.590).In addition, we found that other variables such as the prematurity (aOR, 1.205; 95% CI, 0.335–4.320) and NICU admission rates (aOR, 2.361; 95% CI, 0.456–12.231) were not associated with insufficient weight gain after a GDM diagnosis. Conclusion: Our results indicate that insufficient weight gain after a GDM diagnosis is not a risk factor for SGA, prematurity, and NICU admission rates.